Mutation in JPH2 cause dilated cardiomyopathy. Issue 5 (29th July 2016) - Sabater‐Molina, M.; Navarro, M.; García‐Molina Sáez, E.; Garrido, I.; Pascual‐Figal, D.; González Carrillo, J.; Gimeno Blanes, J.R.
Abstract :